Is there a place for ontological hermeneutics in mental-health nursing research? A review of a hermeneutic study - Kam, Hock Chang; Horrocks, Stephen (Blackwell Publishing Asia Pty Ltd, 2008)
A lot of research carried out within the context of mental-health nursing using qualitative data collection tools claims that it is hermeneutical, with usually just a short section describing the hermeneutical methodology as though it is a very broad philosophical approach. Criticisms of the latter approach more often than not concentrate on the level of the data collection tools without getting to grips with the underlying hermeneutical philosophy. This paper examines the difference between methodological and ontological hermeneutics and then gives an example of a piece of research using the latter approach. It is then argued that criticisms of the hermeneutical approach usually only concentrate on methodological hermeneutics with the consequence that they seriously misapply their criticisms if the research is using ontological hermeneutics.